مصطلحات اتفاقية إسطنبول: تحليلها وتأصيلها الشرعي في ضوء مقاصد الشريعة: Terminology of the Istanbul Convention: An Analysis and Sharia Grounding in Light of Maqasid al-Sharia - Ali Riza Eksi, Muhammed; Ghalia, Bouhedda (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
ملخص البحث تستعرض تتناول هذه الدراسة تحليل بعض المصطلحات الأساسية الواردة في اتفاقية إسطنبول، وعلى رأسها "النوع الاجتماعي" و"الهوية الجندرية" و"الميول الجنسية"، وذلك من خلال قراءة نقدية تقويمية في ضوء مقاصد الشريعة الإسلامية. تنطلق الدراسة من إشكالية مفادها أن هذه المصطلحات لا تمثل مجرد مصطلحات لغوية تنظيمية، بل تعبّر عن خلفيات فلسفية ورؤى اجتماعية ذات امتدادات فكرية وتشريعية عميقة، قد تتعارض في بعض أبعادها مع التصور الإسلامي للأسرة والفطرة الإنسانية. اعتمد البحث المنهج الاستقرائي لدراسة الخلفية التاريخية لنشأة الاتفاقية وأهدافها ونطاق تطبيقها، كما اعتمد المنهج التحليلي لتحليل المصطلحات المذكورة من حيث مدلولاتها المعاصرة ومآلاتها الاجتماعية، مع بيان علاقتها بالبنية المفهومية للاتفاقية. وفي ضوء التأصيل الشرعي، خلصت الدراسة إلى أن بعض هذه المفاهيم، كما تُفهم في سياقها الاتفاقي، تتعارض مع مقاصد الشريعة في حفظ الدين، والنفس، والنسل، والعِرض، وتستند إلى تصور مغاير لطبيعة الفروق بين الرجل والمرأة ووظائفهما داخل الأسرة. ABSTRACT This study undertakes a critical and evaluative analysis of pivotal terms enshrined in the Istanbul Convention, most notably ’gender,’ ’gender identity,’ and ’sexual orientation,’ through the lens of the Higher Objectives of Islamic Law (Maqasid al-Shari’ah). The research is predicated on the premise that these terms are not merely neutral linguistic or administrative markers; rather, they encapsulate philosophical underpinnings and social paradigms with profound intellectual and legislative ramifications that may, in certain dimensions, diverge from the Islamic conception of the family unit and innate human nature (Fitrah). Methodologically, the research employs an inductive approach to investigate the historical genesis, objectives, and jurisdictional scope of the Convention. This is coupled with an analytical methodology to dissect the contemporary connotations and social consequences of the aforementioned terms, while elucidating their interplay with the Convention’s broader conceptual framework. Drawing upon Sharia-based foundational analysis, the study concludes that certain concepts—as interpreted within the treaty’s specific context—clash with the essential Maqasid regarding the preservation of faith, life, progeny, and honor. Furthermore, they are found to be rooted in a worldview that fundamentally differs from the inherent nature of the distinctions between men and women and their respective roles within the family structure.